Evaluation of the Effectiveness of Plant-Protein-Based Cleaning Agents in the Production of Industrial-Filtered Clarified Apple Juice - Julianna Kereszturi; Csenge Béres; István Dalmadi; Mónika Máté (Applied Sciences)
Apple (Malus domestica Borkh.) juice is a globally popular beverage that is valued for its pleasing flavor, wide availability, and health benefits, including support for cardiovascular health and antioxidant properties. A critical element of the production process is the clarification procedure, which improves the product’s purity, visual appeal, and shelf stability by removing solids, colloids, and polyphenols. This study examines the efficacy of plant-based clarifiers, LittoFresh Liquid and FloaClair, in combination with three mineral agents—KlarSol30, GranuBent Pore-Tec, and Seporit Pore-Tec—on the quality of apple juice. The following analytical procedures were conducted: measurement of turbidity (NTU), color stability (ΔE*), transmittance at 440 nm, antioxidant capacity (FRAP), and total polyphenol content (TPC). The results showed that plant-based clarifiers were effective in reducing turbidity by up to 45% while improving transmittance levels by an average of 30% compared to untreated samples. Additionally, plant-based agents retained up to 20% more polyphenols and exhibited a 15% higher antioxidant capacity than traditional gelatin-based clarifiers.